2013
DOI: 10.1021/ac4033214
|View full text |Cite
|
Sign up to set email alerts
|

Native Top-Down Electrospray Ionization-Mass Spectrometry of 158 kDa Protein Complex by High-Resolution Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) delivers high resolving power, mass measurement accuracy, and the capabilities for unambiguously sequencing by a top-down MS approach. Here, we report isotopic resolution of a 158 kDa protein complex - tetrameric aldolase with an average absolute deviation of 0.36 ppm and an average resolving power of ~520,000 at m/z 6033 for the 26+ charge state in magnitude mode. Phase correction further improves the resolving power and average absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
137
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 29 publications
(70 reference statements)
7
137
0
1
Order By: Relevance
“…The work of Li et al illustrates that resolving isotope patterns indeed diminishes the discrepancy between R nat and R max because R nat can now be determined for a single isotope peak rather than for a protein ion peak, that consists of all its isotopes. Though, it is still impossible to separate the isotope distributions of unmodified and adduct-bound species [55]. This is also illustrated in Figure 3, where we simulate the 26+ charge state of a 150 kDa "Averagine" protein (1,350 Averagine residues [61]) in its unmodified, ammonium-bound and sodium-bound form.…”
Section: Native Ms Cannot Resolve Binding Of Salt and Buffer Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…The work of Li et al illustrates that resolving isotope patterns indeed diminishes the discrepancy between R nat and R max because R nat can now be determined for a single isotope peak rather than for a protein ion peak, that consists of all its isotopes. Though, it is still impossible to separate the isotope distributions of unmodified and adduct-bound species [55]. This is also illustrated in Figure 3, where we simulate the 26+ charge state of a 150 kDa "Averagine" protein (1,350 Averagine residues [61]) in its unmodified, ammonium-bound and sodium-bound form.…”
Section: Native Ms Cannot Resolve Binding Of Salt and Buffer Moleculementioning
confidence: 99%
“…In contrast, the highest R nat achieved with these same mass analyzers is reduced to much lower values, ranging from 1,500 (on a TOF) [52] to about 5,500 (on an Orbitrap) [23]. Using a FTICR mass spectrometer equipped with a distinctive ParaCell [53,54], Li et al were able to obtain isotope resolution on native 158 kDa tetrameric aldolase (R ≈ 520,000) [55]. Here, we adopt a more conservative estimation of R max = 40,000 for most currently used FTICR analyzers.…”
Section: Boundaries Of the Apparent Mass Resolution In The High Mass mentioning
confidence: 99%
“…As an alternative to these methods,w ee xplore the potential of native top-down mass spectrometry (MS) using electrospray ionization (ESI) [6] fort he characterization of RNA-protein interactions.P revious studies showed that native ESI can produce gaseous RNA-protein or RNAligand complexes, [7] and in top-down MS experiments using collisionally activated dissociation (CAD), Loo [8] and Fabris [7f] observed cleavage of covalent mononucleotide phosphate and RNAp hosphodiester bonds,r espectively,r ather than dissociation of the noncovalent bonds of the complexes studied. In agreement with our recent work on KIX protein [9] and data from the literature, [10] their findings suggest that in the absence of solvent, the strength of salt bridges can be comparable to that of covalent bonds.Bycontrast, desolvated duplexes of small interfering RNAthat are stabilized by base pairing and stacking instead of salt-bridge interactions were found to dissociate by strand separation rather than backbone bond cleavage.…”
mentioning
confidence: 99%
“…We instead attribute this phenomenon to charge redistribution within fragment ions by proton transfer according to Coulombic repulsion, [18] after backbone cleavage but before complex dissociation, that can weaken or strengthen individual interactions differently in different fragment ions,which in turn affects the competition between complementary c and y fragments for tat. In this scenario,anelectrostatic interaction of residue 6ofc 6 with tat can be sufficiently strong to compete with the interactions between the complementary fragment y 25 and tat, whereas in the c 7 , c 8 ,a nd c 9 ions,n egative charge will move away from residue 6t ot he terminal residues 7, 8, and 9, respectively, [18] thus weakening the electrostatic interaction of residue 6with tat. This does not exclude the possibility of tat interactions with residues 7, 8, and 9b ut suggests that they must be substantially weaker than that between tat and residue 6ofc 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation